POLAR PHASE INSTABILITY IN THE PARAELECTRIC REGION OF PMN-PT RELAXOR FERROELECTRIC CRYSTALS - Shabbir, G. (The Nucleus, 2014)
The phase instabilities in the (1-x)Pb(Mg1/3Nb2/3)-xPbTiO3 (PMN-xPT) relaxor ferroelectric single crystals with orientations [110] and [111] were investigated as a function of temperature and dc-bias voltage. The composition of crystals was in the range of morphotropic phase boundary (MPB) region with x 0.33. Two structural phase transition anomalies were observed in the temperature dependent capacitance of the two crystals related to paraelectric cubic to ferroelectric tetragonal and then to rhombohedral/monoclinic symmetry changes. A remarkable shift in the cubic-tetragonal phase transition boundary towards the higher temperature side was observed with increasing bias voltage. The origin of this dc-bias assisted unusual instability, apparently inside the cubic phase, was associated to the presence and complex dynamics of polar nanoregions (PNRs).